2013
DOI: 10.1021/ja410291u
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Cellulose Hydrolysis by a Two-Step, Retaining Cellobiohydrolase Elucidated by Structural and Transition Path Sampling Studies

Abstract: Glycoside hydrolases (GHs) cleave glycosidic linkages in carbohydrates, typically via inverting or retaining mechanisms, the latter of which proceeds via a two-step mechanism that includes formation of a glycosyl-enzyme intermediate. We present two new structures of the catalytic domain of Hypocrea jecorina GH Family 7 cellobiohydrolase Cel7A, namely a Michaelis complex with a full cellononaose ligand and a glycosyl-enzyme intermediate, that reveal details of the 'static' reaction coordinate. We also employ tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
254
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(272 citation statements)
references
References 50 publications
15
254
1
2
Order By: Relevance
“…This is over an order of magnitude less than k cat for the same system (4.8 s Ϫ1 ) (24), and we will therefore not consider this parameter further in the discussion of rate limitation. We note, however, that the above arguments pertain to hydrolysis by monocomponent TrCel7A, and different conclusions regarding k cat may be reached for mixtures of synergistically acting cellulases (21,55). Hence, Jalak et al (21) found that hydrolysis of bacterial cellulose by an optimally composed mixture of Cel7A and the endo-active enzyme Cel5A could reach a specific hydrolysis rate at steady state (about 2 s Ϫ1 ), which was close to the rate constant for the inner catalytic cycle (including hydrolysis, product expulsion, and processive movement).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This is over an order of magnitude less than k cat for the same system (4.8 s Ϫ1 ) (24), and we will therefore not consider this parameter further in the discussion of rate limitation. We note, however, that the above arguments pertain to hydrolysis by monocomponent TrCel7A, and different conclusions regarding k cat may be reached for mixtures of synergistically acting cellulases (21,55). Hence, Jalak et al (21) found that hydrolysis of bacterial cellulose by an optimally composed mixture of Cel7A and the endo-active enzyme Cel5A could reach a specific hydrolysis rate at steady state (about 2 s Ϫ1 ), which was close to the rate constant for the inner catalytic cycle (including hydrolysis, product expulsion, and processive movement).…”
Section: Discussionmentioning
confidence: 74%
“…We chose Trp-38 as target for a low affinity mutant because this residue has previously been shown to interact with the cellulose chain (8,26). Moreover, it is located in the middle of the tunnel quite far from the scissile bond unlike, for example, Trp-367 and Trp-376, which are directly involved in the twist of the cellulose strand that is important for the actual catalysis (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellulosic substrate chain has to travel through the tunnel, where ␤-1,4-glycosyl bonds of cellobiose molecules (dimers) are hydrolyzed off the ends (GH6 or GH7 enzymes). The three-dimensional structures are for Trichoderma reesei GH6 (CBHII; PDB entry 1QK2) (108) and GH7 (CBHI or Cel7A; PDB entry 4C4C) enzymes (227).…”
Section: Cellulasesmentioning
confidence: 99%
“…The structures of GH7 catalytic domains are known from 10 CBHs, Trichoderma reesei Cel7A (TreCel7A) (12)(13)(14), Heterobasidion irregulare Cel7A (HirCel7A) (15), Phanerochaete chrysosporium Cel7D (PchCel7D) (16), Talaromyces emersonii Cel7A (RemCel7A) (17), Trichoderma harzianum Cel7A (ThaCel7A) (18), Melanocarpus albomyces Cel7B (MalCel7B) (19), Aspergillus fumigatus Cel7A (AfuCel7A) (20), Humicola grisea var. thermoidea Cel7A (HgtCel7A) (21) Limnoria quadripunctata Cel7B (LquCel7B) (22), and Geotrichum candidum Cel7A (23), and three endoglucanases (EGs), T. reesei Cel7B (24), Humicola insolens Cel7B (25), and Fusarium oxysporum Cel7B (26).…”
mentioning
confidence: 99%